Correlation between Microstructure and Hardfacing Properties with Welding Current Intensity in Reconditioned Low-alloy Steel Material using Submerged Arc Welding (SAW) : A Comprehensive Review - asmara, iman Nugraha; Winarto, Winarto (Journal of Materials Exploration and Findings, 2025)
This review studying the correlation between microstructural transformations and mechanical properties in reconditioned low-allow steel material, focusing on the impact of Submerged Arc Welding (SAW) parameters, especially current, on microstructure . The study highlights how variation on welding parameters, especially current intensity variation, affecting microstructural transformations, hardness, and wear resistance of hardfaced layers. Key aspects such as dilution effect, phases distribution, and carbide formation are reviewed to understanding their impact on mechanical properties. By reviewing insights from existing literature and experimental findings, this review underscores the role of Submerged Arc Welding in enhancing mechanical properties and microstructural of low-alloy steel material.